Ceramide and Sphingosine-1-Phosphate in Cell Death Pathways : Relevance to the Pathogenesis of Alzheimer's Disease - Shubhra Chakrabarti, Sankha; Bir, Aritri; Poddar, Jit; Sinha, Maitrayee; Ganguly, Anirban; Chakrabarti, Sasanka (Current Alzheimer Research, 2016)
The metabolic turnover of sphingolipids produces several signaling molecules that profoundly affect the proliferation, differentiation and death of cells. In particular, an enormous body of information is available that defines the varied role of ceramide and sphingosine-1-phosphate in cell death and survival. This review specifically examines the role of ceramide and sphingosine-1- phosphate in triggering neuronal death in Alzheimer's disease by analyzing the data from post-mortem studies and experimental research. There is compelling evidence that ceramide plays a key role in the neurodegeneration and amyloidogenesis occurring in the brain in Alzheimer's disease. Further, it appears that ceramide and amyloid beta protein orchestrate an attack on mitochondria to set in the pathways of cell death. However, the complexity of metabolic and signaling pathways of sphingolipid derivatives precludes an immediate identification of effective drug targets for the therapy of Alzheimer's disease.
Keywords: Apoptosis